Hypoxia Sensing of β-Adrenergic Receptor Is Regulated by Endosomal PI3Kγ. Issue 6 (13th February 2023) - Sun, Yu; Stenson, Kate; Mohan, Maradumane L.; Gupta, Manveen K.; Wanner, Nick; Asosingh, Kewal; Erzurum, Serpil; Naga Prasad, Sathyamangla V.
Abstract : Background: Impaired beta-adrenergic receptor (β1 and β2AR) function following hypoxia underlies ischemic heart failure/stroke. Activation of PI3Kγ (phosphoinositide 3-kinase γ) by beta-adrenergic receptor leads to feedback regulation of the receptor by hindering beta-adrenergic receptor dephosphorylation through inhibition of PP2A (protein phosphatase 2A). However, little is known about PI3Kγ feedback mechanism in regulating hypoxia-mediated β1 and β2AR dysfunction and cardiac remodeling. Methods: Human embryonic kidney 293 cells or mouse adult cardiomyocytes and C57BL/6 (WT) or PI3Kγ knockout (KO) mice were subjected to hypoxia. Cardiac plasma membranes and endosomes were isolated and evaluated for β1 and β2AR density and function, PI3Kγ activity and β1 and β2AR-associated PP2A activity. Metabolic labeling was performed to assess β1 and β2AR phosphorylation and epinephrine/norepinephrine levels measured post-hypoxia. Results: Hypoxia increased β1 and β2AR phosphorylation, reduced cAMP, and led to endosomal accumulation of phosphorylated β2ARs in human embryonic kidney 293 cells and WT cardiomyocytes. Acute hypoxia in WT mice resulted in cardiac remodeling and loss of adenylyl cyclase activity associated with increased β1 and β2AR phosphorylation. This was agonist-independent as plasma and cardiac epinephrine and norepinephrine levels were unaltered. Unexpectedly, PI3Kγ activity was selectively increased in the endosomes of human embryonic kidney 293 cells and WT hearts post-hypoxia. Endosomal β1- and β2AR-associated PP2A activity was inhibited upon hypoxia in human embryonic kidney 293 cells and WT hearts showing regulation of beta-adrenergic receptors by PI3Kγ. This was accompanied with phosphorylation of endogenous inhibitor of protein phosphatase 2A whose phosphorylation by PI3Kγ inhibits PP2A. Increased β1 and β2AR-associated PP2A activity, decreased beta-adrenergic receptor phosphorylation, and normalized cardiac function was observed in PI3Kγ KO mice despite hypoxia. Compared to WT, PI3Kγ KO mice had preserved cardiac response to challenge with β1AR-selective agonist dobutamine post-hypoxia. Conclusions: Agonist-independent activation of PI3Kγ underlies hypoxia sensing as its ablation leads to reduction in β1- and β2AR phosphorylation and amelioration of cardiac dysfunction.